Comparative study on conductivity using Polarization and Depolarization Current (PDC) test for HV Insulation - Jamaii, N. A. M.; Piah, M. A. M.; Muhamad, N. A. (2011)
Polarization a nd Depolarization C urrent (PDC) t esting is a no n-destructive d ielectric t esting method t 0 de termine t he conductivity 0 f i nsulations. J t is 0 ne 0 ft he dielectric d iagnostic techniques based 0 n t ime do main measurement. P DC measurement technique has gained immense popularity due to its ability t 0 a ssess t he condition 0 f H V i nsulation. PDC measurement can p rovide information a bout the conductivity within the i nitial periods (seconds) after a DC step voltage application. This p aper p resent t he r eview a nd c omparison results f rom s everal published papers 0 n application 0 f P DC method i n f inding t he c onductivity 0 ft he v arious t ypes 0 f insulators. T he s cope 0 ft he review co vered solid and l iquid insulations t ypes. I n this paper, f or s olid i nsulation the s tudied was f ocused 0 n c ables i nsulations, el ectric machine s tator insulation and paper i nsulator in p ower t ransformer i nsulation. For l iquid i nsulation, the r eview a nd c omparison was done on the biodegradable and mineral t ransformer 0 ils. T h e r e view results show that the P DC technique s uccessfully g ive indication on level of conductivity of the HV insulation materials.